Investigating Influences of Synthesizing Eco-Friendly Waste-Coir-Fiber Nanofiller-Based Ramie and Abaca Natural Fiber Composite Parameters on Mechanical Properties - T. Sathish; Vinayagam Mohanavel; Palanivel Velmurugan; R. Saravanan; T. Raja; M. Ravichandran; Wadi B. Alonazi; Shanmugam Sureshkumar; Atkilt Mulu Gebrekidan (Bioinorganic Chemistry and Applications)
Clean technology-based natural fiber composite fabrication is the prime aim of this piece of research. Natural fibers highly replace metal usage in industries and automobile, marine, medical applications, and so on. Vast amounts of natural fibers are freely available in all areas. In this research, work nanofiller material such as nano form waste coir fiber is collected from used car seat. The 10 wt.% of nanofiller material is added to the preparation of natural nanocomposites (ramie and abaca fiber). Hybrid composites are fabricated with the influence of different process parameters, namely, fiber weight percentage (20 wt.%, 30 wt.%, 40 wt.%, and 50 wt.%), NaOH action % (4%, 6%, 8%, and 10%), compression pressure (9 MPa, 12 MPa, 15 MPa, and 18 MPa), and temperature (100°C, 120°C, 140°C, and 160°C). Furthermore, the strength of this hybrid composite has analyzed by conducting flexural, impact, and shore hardness tests. These tests have provided the influence of selected parameters and their effects on the results of experimental work. In the flexural analysis, 6% of NaOH action has offered maximum flexural strength of the specimens. Correspondingly in the impact test, 30 wt.% of fiber is produced higher impact strength. Finally, applying 15 Mpa of compression pressure records the maximum shore hardness.